Radiological exploration of varicocele. - D’Ottavio, Gianfranco (Acta Médica Portuguesa, 1979)
After a survey of the different techniques which are now employed in a radiological exploration of idiopathic varicocele, the technique of pre-operative ascending trans-scrotal venography is analysed. Radiograms of 94 venographies are presented and discussed. A classification of the normal data and anomalies which were observed with this technique is proposed. Based in such observations the use of pre-operative trans-scrotal venography is recommended as a stage of primary importance in the varicocele surgical treatment. In fact, the peculiar polymorfism of the testicular venous retourn and the presence of several anastomotic vessels can be considered as possible cause either of a recurrence of pathology, or of a bilateral inhibition of spermatogenesis.